PENGARUH KARAKTERISTIK PENGHUNI LAPAS TERHADAP TINDAKAN BERISIKO HIV-AIDS DI LAPAS KELAS IIB LUBUK PAKAM - Efrina Purba; Ida Yustina; Fauzi . (Kebijakan, Promosi Kesehatan dan Biostatiskik, 2012)
ABSTRACT HIV-AIDS (Human Immunodeficiency Virus-Acquired Immune Deficiency Syndrome) is a global issue which is faced by almost all of the countries in the world especially those belong to the developing countries including Indonesia. Based on the report of UNAIDS (2009), the number of HIV sufferers in the world has reached 33.3 millions persons and those who died because of AIDS reached 1.8 million persons Lubuk Pakam penitentiary is a place which is at risk of spreading HIV because risky behavior exists in this correctional facility. The purpose of this explanatory survey study was to analyze the influence of characteristics (age, sex, education, previous occupation, kinds of problem, length of sentence, knowledge and attitude) of the inmates in this penitentiary on the HIV-AIDS-risk action in the Penitentiary Class II B Lubuk Pakam, Deli Serdang District in 2011. The populations of this study were all of the 928 inmates in this Penitentiary and 90 inmates were selected to be the samples for this study. The data for this study were obtained through questionnaire distribution and then were analyzed through multiple linear regression tests. The result of this study showed that the variables with the most significant influence on the HIV-AIDS-risk action were age, education, kinds of problem, length of sentence, knowledge and attitude. The variables which had no influence were sex and previous occupation